A new species of the genus Tyrictaca Walker, 1862 (Lepidoptera: Sesiidae) from West Malaysia with a catalogue of the genus - Gorbunov, Oleg G. (Zootaxa, 2022)
A new species, Tyrictaca pulchra O. Gorbunov sp. nov., is described and illustrated from West Malaysia. The female and the larval host plant are still unknown. Ceratocorema woodstocki Liang & Hsu, 2017 is transferred from the genus Tyrictaca Walker, 1862 to the genus Entrichella Bryk, 1947. An annotated catalogue of the genus Tyrictaca is provided.